Polymorphism in codon 17 of the CTLA-4 gene (+49 A/G) is not associated with susceptibility to rheumatoid arthritis in British Caucasians. - Milicic, A; Brown, M; Wordsworth, B (2001)
The role of the CTLA-4 antigen in the development of autoimmune diseases is well documented, with several autoimmune disorders showing association or linkage with the CTLA-4 locus. Its role in the aetiology of rheumatoid arthritis (RA) however, remains unclear, as the functional studies of the B7-CTLA-4 pathway in mouse models of RA and genetic studies in humans have given contrasting results. We have studied the single nucleotide polymorphism at position +49 (A/G) of the CTLA-4 gene, in a cohort of 421 RA cases and 452 healthy controls from the UK. Despite the high statistical power to detect even a weak susceptibility effect, no significant association was found. We also analysed the distribution of the allele and genotype frequencies with respect to the presence of the shared epitope (a known RA susceptibility factor) and found no statistically significant differences. We conclude that, although the importance of the B7-CTLA-4 interaction in the development of RA can not be excluded, the CTLA-4 gene is unlikely to be a predisposing factor to this disease.